If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4n(5n + 1) = 4 Reorder the terms: -4n(1 + 5n) = 4 (1 * -4n + 5n * -4n) = 4 (-4n + -20n2) = 4 Solving -4n + -20n2 = 4 Solving for variable 'n'. Reorder the terms: -4 + -4n + -20n2 = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -4n + -20n2 = 0 Factor out the Greatest Common Factor (GCF), '-4'. -4(1 + n + 5n2) = 0 Ignore the factor -4.Subproblem 1
Set the factor '(1 + n + 5n2)' equal to zero and attempt to solve: Simplifying 1 + n + 5n2 = 0 Solving 1 + n + 5n2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. 0.2 + 0.2n + n2 = 0 Move the constant term to the right: Add '-0.2' to each side of the equation. 0.2 + 0.2n + -0.2 + n2 = 0 + -0.2 Reorder the terms: 0.2 + -0.2 + 0.2n + n2 = 0 + -0.2 Combine like terms: 0.2 + -0.2 = 0.0 0.0 + 0.2n + n2 = 0 + -0.2 0.2n + n2 = 0 + -0.2 Combine like terms: 0 + -0.2 = -0.2 0.2n + n2 = -0.2 The n term is n. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. 0.2n + 0.25 + n2 = -0.2 + 0.25 Reorder the terms: 0.25 + 0.2n + n2 = -0.2 + 0.25 Combine like terms: -0.2 + 0.25 = 0.05 0.25 + 0.2n + n2 = 0.05 Factor a perfect square on the left side: (n + 0.5)(n + 0.5) = 0.05 Calculate the square root of the right side: 0.223606798 Break this problem into two subproblems by setting (n + 0.5) equal to 0.223606798 and -0.223606798.Subproblem 1
n + 0.5 = 0.223606798 Simplifying n + 0.5 = 0.223606798 Reorder the terms: 0.5 + n = 0.223606798 Solving 0.5 + n = 0.223606798 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + n = 0.223606798 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + n = 0.223606798 + -0.5 n = 0.223606798 + -0.5 Combine like terms: 0.223606798 + -0.5 = -0.276393202 n = -0.276393202 Simplifying n = -0.276393202Subproblem 2
n + 0.5 = -0.223606798 Simplifying n + 0.5 = -0.223606798 Reorder the terms: 0.5 + n = -0.223606798 Solving 0.5 + n = -0.223606798 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + n = -0.223606798 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + n = -0.223606798 + -0.5 n = -0.223606798 + -0.5 Combine like terms: -0.223606798 + -0.5 = -0.723606798 n = -0.723606798 Simplifying n = -0.723606798Solution
The solution to the problem is based on the solutions from the subproblems. n = {-0.276393202, -0.723606798}Solution
n = {-0.276393202, -0.723606798}
| 5-y/12=1 | | 1/4x-7=7 | | -23+10x=37+8x | | 3/4x-15=-9 | | 4/9=1/x | | 10+4x-3=70 | | 8=7x-10 | | -5(3n+3)=20 | | 31=26-2c | | x=2x+90-x-12 | | 4x^2-4x-16/9=0 | | 4x^2-4x-16/9 | | f(9a)=x-2 | | 8k+30=6 | | 22=4x+1 | | 3-20x^3=0 | | Y=2.54 | | -500+2D+D=3400 | | y=(1/10)x-7 | | x+3=4(x-3)+3 | | 3(2a-b)-7(2b-6a)= | | (2^7)^4/2^30 | | 1800/9=x | | x/19=361 | | 7x-14y=14 | | (-a-7b+2)2ab= | | 4x-8(0)=32 | | A+ab+abc+abcd=1992 | | 10-(6x+2)=2x-8 | | 10-(6x+2)=2c-8 | | 10-1/4(8x-12)=1/2(2x-4) | | 6[4a-2a(2a+4b)+4a^2]= |